2013
DOI: 10.4012/dmj.2012-328
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a portable microhardness testing system (Cariotester) for diagnosis of progression in active caries lesions

Abstract: This study aimed to evaluate the validity of a portable microhardness testing system (Cariotester) for diagnosis of progression in active caries lesions by comparing data from this device and a laser fluorescence device (DIAGNOdent). Carious dentin in 12 specimens (stained clearly with a caries detector dye) was incrementally removed with a round bur at 150 μm depth intervals from the dentin surface in the direction of the pulp chamber. After each increment (total 138 sites), the Knoop hardness (HK) (evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Although, the caries-affected dentin results obtained in the present study follow a clinical protocol, care was taken to minimize the variability by standardizing the Knoop hardness using a manual system to determine hardness. This instrument was validated by a study that compared it with a fluorescent laser device (DIAGNOdent, KAVO, Biberach, Germany) 14) . In the study referred to, an inverse relationship was found between the Knoop hardness obtained by Cariotester and the fluorescence obtained by Diagnodent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the caries-affected dentin results obtained in the present study follow a clinical protocol, care was taken to minimize the variability by standardizing the Knoop hardness using a manual system to determine hardness. This instrument was validated by a study that compared it with a fluorescent laser device (DIAGNOdent, KAVO, Biberach, Germany) 14) . In the study referred to, an inverse relationship was found between the Knoop hardness obtained by Cariotester and the fluorescence obtained by Diagnodent.…”
Section: Discussionmentioning
confidence: 99%
“…The indenter is painted white, and, after the indentation procedure, the length (µm) of the part that has lost its paint is visualized in an optical-microscope; this length is then converted into Knoop hardness automatically by the own program of this system. This equipment allows dental substrate hardness to be measured, regardless of shape or angle, or even in vivo or in vitro situations [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that initial samples from soft and wet lesions harbored significantly more bacteria, including Lactobacilli and Streptococcus mutans, than samples from medium, hard, or dry lesions 20) , and that infected dentin is decalcified, softened, and devoid of its remineralization ability 5,[19][20][21][22][23] . With respect to the evaluation of carious dentin, previous studies used the KHN as a measure of softened dentin hardness and Ca/P mass ratio as one of the mineral components 2,3,13,15,[24][25][26] . Therefore, we evaluated the qualitative relationship between the applied voltage and residual dentin in constant-speed moving injection measuring KHN (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1). Several in vitro and in vivo studies have examined the hardness of dentin using the Cariotester [5][6][7][8] . The first objective of this study is to reveal the relationship between the indentation depth determined by a Cariotester with an enamel indenter and the Knoop hardness (KHN) determined by a microhardness tester.…”
Section: Introductionmentioning
confidence: 99%